Inovasi Bupati di Ruang Demokrasi: Upaya Membangun Kesadaran Inovasi Birokrasi - Widiyahseno, Bambang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2015)
Decentralization and granting broad autonomy to the local government open the space for the continuity of policy innovation. This study is important because not all regional heads could do it. There are many parties involved and interested in the process. This study explores the behavior of regents to build awareness and mindset (unfreezing) to various parties. The magnitude of opportunities to innovate is largely determined by regent ability to perform the process of unfreezing. The findings indicate a regentâs effort in building relationships with various parties, especially the power of the bureaucracy, parliament and society (the public) in the process of unfreezing ie melting of the ice or the awareness of the need for change (innovation). Those are Strategies to encourage and initiate innovation to anticipate the bureaucracy, which is building a coalition with the community to deal with the inert bureaucracy.